2013
DOI: 10.3945/an.113.003798
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-α as a Key Nutritional and Environmental Sensor for Metabolic Adaptation

Abstract: Peroxisome proliferator-activated receptors (PPARs) are transcription factors that belong to the superfamily of nuclear hormone receptors and regulate the expression of several genes involved in metabolic processes that are potentially linked to the development of some diseases such as hyperlipidemia, diabetes, and obesity. One type of PPAR, PPAR-α, is a transcription factor that regulates the metabolism of lipids, carbohydrates, and amino acids and is activated by ligands such as polyunsaturated fatty acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(162 citation statements)
references
References 130 publications
(152 reference statements)
4
148
0
3
Order By: Relevance
“…It is known that PPARa functions as a lipid sensor in the liver and recognizes and responds to the influx of fatty acids by stimulating the transcription of specific genes related to lipid metabolism (Contreras et al 2013). Also, there is evidence that Ppara-null mice develop lipid steatosis (Costet et al 1998) due to decreased capacity to oxidize fatty acids.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that PPARa functions as a lipid sensor in the liver and recognizes and responds to the influx of fatty acids by stimulating the transcription of specific genes related to lipid metabolism (Contreras et al 2013). Also, there is evidence that Ppara-null mice develop lipid steatosis (Costet et al 1998) due to decreased capacity to oxidize fatty acids.…”
Section: Resultsmentioning
confidence: 98%
“…PPARα is activated by energy deprivation, fasting, and fibrate agents. It is expressed primarily in the liver, heart, kidney and intestine [7,8]. Transcriptional regulation is achieved by the binding of PPAR/retinoid X receptor heterodimers to PPAR response elements (PPREs) in target gene promoters [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, alcohol treatment increased CRBN gene expression by suppressing the PPARα-dependent pathway, suggesting that PPARα is a negative transcriptional regulator of CRBN. PPARα is an important lipid sensor in the liver that responds to different metabolic conditions [12], which could explain why CRBN responds to metabolic conditions and regulates AMPK activity. An early study of CRBN demonstrated that hypoxia/ reoxygenation (H/R) and ROS stimulation enhance mRNA and protein expression of CRBN in neuroblastoma cells [42].…”
Section: Potential Regulators Of Crbn Expressionmentioning
confidence: 99%